Enhancing Critical Thinking Skills in Poetry Writing through Nature-Based Learning Method - Khalsiah, Khalsiah; Alfiadi, Teuku; Safriandi, Safriandi; Fatmawati, Fatmawati (JETLEE: Journal of English Language Teaching, Linguistics, and Literature, 2025)
To improve poetry writing skills, it is necessary to use a variety of strategies that encourage students to think critically and conduct in-depth examination. This strategy can considerably increase their originality and proficiency in poetry writing. The Nature-Based Learning Method is used in this study to improve critical thinking abilities, specifically those related to poetry writing. This quasi-experimental study assesses the impact of specific activities under controlled conditions. To ensure accurate and trustworthy data collection, the study employs a Pretest-Posttest Control Group Design, with a pretest administered prior to treatment and a posttest administered thereafter in both the experimental and control groups. The study included 63 students from Malikussaleh University, chosen by purposive sampling. The major data collection tool was a poetry-writing performance exam. Normality, homogeneity, and hypothesis tests were used during the data analysis. The t-test for students' poetry writing skills yielded a significant value of 0.000 < 0.05, rejecting the null hypothesis (Ho) and accepting the alternative hypothesis (Ha). In the experimental group, the average pretest score for poetry writing skills was 53.38, but it climbed to 80.65 following the intervention. Similarly, the control group's average critical thinking abilities score for poetry writing increased from 48.90 on the pretest to 67.65 on the posttest. These findings imply that by improving critical thinking skills, particularly in writing, students can considerably improve their capacity to write high-quality poetry. This enhancement in critical thinking is believed to boost problem-solving abilities and help to create more refined and compelling poetry compositions.